Wilhelm Hensel und Fanny Hensel, geb. Mendelssohn-Bartholdy - Weger, August, 1823-1892 (engraver):::Creator::::::::::::; Singer, Johann-Paul, 1823-before 1900 (engraver):::Contributor:::::::::::: (Germany; Leipzig)
Portrait engraving of Fanny Hensel (sister of Felix Mendelssohn) and her husband Wilhelm.